Mathematics for informatics and computer science - Audibert, Pierre, 1941- (ISTE., 2013)
How many ways do exist to mix different ingredients, how many chances to win a gambling game, how many possible paths going from one place to another in a network? To this kind of questions Mathematics applied to computer gives a stimulating and exhaustive answer. This text, presented in three parts (Combinatorics, Probability, Graphs) addresses all those who wish to acquire basic or advanced knowledge in combinatorial theories. It is actually also used as a textbook.